2004
DOI: 10.1074/jbc.m306041200
|View full text |Cite
|
Sign up to set email alerts
|

γ-Secretase Activity of Presenilin 1 Regulates Acetylcholine Muscarinic Receptor-mediated Signal Transduction

Abstract: Familial Alzheimer's disease (FAD) presenilin 1 (PS1) mutations give enhanced calcium responses upon different stimuli, attenuated capacitative calcium entry, an increased sensitivity of cells to undergo apoptosis, and increased ␥-secretase activity. We previously showed that the FAD mutation causing an exon 9 deletion in PS1 results in enhanced basal phospholipase C (PLC) activity (Cedazo-Minguez, A., Popescu, B. O., Ankarcrona, M., Nishimura, T., and Cowburn, R. ] i responses to levels found in PS1 D257A or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 52 publications
(78 reference statements)
1
15
0
Order By: Relevance
“…This result is in accord with speculations by other investigators who have reported that the perturbation of intracellular calcium homeostasis through RyR may be critical for mutant PS1-induced PC12 and cortical neuronal cell death in response to various stimuli and conditions (9,(16)(17)(18). Similarly, the increased vulnerability of the cells by the elevated intracellular calcium from RyR was also found in the SH-SY5Y neuroblastoma cells, as well as neurons carrying mutant PS1 (36,37). Schneider et al (38) also reported that neuronal cell death of PS2 mutant mice was also prevented with dantrolene.…”
Section: Discussionsupporting
confidence: 92%
“…This result is in accord with speculations by other investigators who have reported that the perturbation of intracellular calcium homeostasis through RyR may be critical for mutant PS1-induced PC12 and cortical neuronal cell death in response to various stimuli and conditions (9,(16)(17)(18). Similarly, the increased vulnerability of the cells by the elevated intracellular calcium from RyR was also found in the SH-SY5Y neuroblastoma cells, as well as neurons carrying mutant PS1 (36,37). Schneider et al (38) also reported that neuronal cell death of PS2 mutant mice was also prevented with dantrolene.…”
Section: Discussionsupporting
confidence: 92%
“…A role for PS1 in the regulation of muscarinic receptormediated signal transduction has also been suggested (55). Here, we show the cell surface colocalization of PS1 and AChE in COS-7 cells in addition to their predominant perinuclear colocalization.…”
Section: Discussionmentioning
confidence: 66%
“…The ApoE genotype is a known factor for AD [92], and inflammation [93], vascular factors [94], oxidative stress and synaptic dysfunction [95], alterations in cell signalling [96] and sensitization to cell death [97] all appear to be important pathogenic mechanisms. Many of these factors are encountered in other dementia types, mainly in VD, therefore giving rationale for the concept that most of the dementia cases in fact have a mixed origin [54].…”
Section: Blood-brain Barrier In Alzheimer's Diseasementioning
confidence: 99%